Given polynomial
.
(a) To show that (x – 3) is a factor of f(x).
Factor theorem:
<em>A polynomial f(x) has a factor of (x – a), if and only if f(a) = 0.</em>
![f(x)=4 x^{3}-12 x^{2}+2 x-6](https://tex.z-dn.net/?f=f%28x%29%3D4%20x%5E%7B3%7D-12%20x%5E%7B2%7D%2B2%20x-6)
![f(3)=4 (3)^{3}-12 (3)^{2}+2 (3)-6](https://tex.z-dn.net/?f=f%283%29%3D4%20%283%29%5E%7B3%7D-12%20%283%29%5E%7B2%7D%2B2%20%283%29-6)
![=4(27)-12(9)+6-6](https://tex.z-dn.net/?f=%3D4%2827%29-12%289%29%2B6-6)
![=108-108](https://tex.z-dn.net/?f=%3D108-108)
= 0
f(3) = 0
Hence (x – 3) is a factor of f(x).
(b) ![f(x)=0](https://tex.z-dn.net/?f=f%28x%29%3D0)
![4 x^{3}-12 x^{2}+2 x-6=0](https://tex.z-dn.net/?f=4%20x%5E%7B3%7D-12%20x%5E%7B2%7D%2B2%20x-6%3D0)
Here
is common in first 2 terms and 2 is common in next 2 terms.
![4x^2(x-3 )+2 (x-3)=0](https://tex.z-dn.net/?f=4x%5E2%28x-3%20%29%2B2%20%28x-3%29%3D0)
Now, (x – 3) is common in both terms.
![(x-3)(4x^2+2)=0](https://tex.z-dn.net/?f=%28x-3%29%284x%5E2%2B2%29%3D0)
and ![(4x^2+2)=0](https://tex.z-dn.net/?f=%284x%5E2%2B2%29%3D0)
x = 3 and ![4x^2+2=0](https://tex.z-dn.net/?f=4x%5E2%2B2%3D0)
3 is the real root.
using quadratic formula solve
and find the other roots.
![$x=\frac{-b \pm \sqrt{b^{2}-4 a c}}{2 a}](https://tex.z-dn.net/?f=%24x%3D%5Cfrac%7B-b%20%5Cpm%20%5Csqrt%7Bb%5E%7B2%7D-4%20a%20c%7D%7D%7B2%20a%7D)
![$x=\frac{-0 \pm \sqrt{0^{2}-4 (4) (2)}}{2 (4)}](https://tex.z-dn.net/?f=%24x%3D%5Cfrac%7B-0%20%5Cpm%20%5Csqrt%7B0%5E%7B2%7D-4%20%284%29%20%282%29%7D%7D%7B2%20%284%29%7D)
![$x=\pm\frac{\sqrt{-32}}{8}](https://tex.z-dn.net/?f=%24x%3D%5Cpm%5Cfrac%7B%5Csqrt%7B-32%7D%7D%7B8%7D)
![$x=\pm\frac{4\sqrt{2}i}{8}](https://tex.z-dn.net/?f=%24x%3D%5Cpm%5Cfrac%7B4%5Csqrt%7B2%7Di%7D%7B8%7D)
![$x=\pm\frac{\sqrt{2}i}{2}](https://tex.z-dn.net/?f=%24x%3D%5Cpm%5Cfrac%7B%5Csqrt%7B2%7Di%7D%7B2%7D)
These are complex roots.
Hence 3 is the only real root of the equation f(x) = 0.